2020
DOI: 10.1002/jhet.4163
|View full text |Cite
|
Sign up to set email alerts
|

Construction, characterization, and antimicrobial evaluation of the novel heteroannulated chromeno[2′′,3′′:6′,5′]pyrido[2′,3′‐d] [1,3] thiazolo[3,2‐a]pyrimidines

Abstract: The reaction of chromone‐3‐carbonitrile with thiobarbituric acid afforded 2‐thioxochromeno[3′,2′:5,6]pyrido[2,3‐d]pyrimidine‐4,6(1H,3H)‐dione, which utilized as a building block for construction of a novel heteroannulated compounds containing chromenopyridothiazolopyrimidine moiety. Reactions of the starting compound with a variety of bielectrophilic reagents namely; chloroacetonitrile, bromomalononitrile, 3‐chloropentanedione, ethyl 2‐chloro‐3‐oxobutanoate, phenacyl bromide, chloroacetic acid, dibromoethane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A literature survey revealed that pyrido [2,3- d ] pyrimidine derivatives have important potential in pharmaceutical and medicinal chemistry due to their diverse range of biological activity, including anti-viral properties [ 1 ], antioxidant [ [2] , [3] , [4] , [5] ], antimicrobial [ [6] , [7] , [8] ], anti-inflammatory [ [9] , [10] , [11] ], antitubercular [ 12 ], it is also used as an inhibitor of some enzymes such as dihydrofolate reductase inhibition [ 13 , 14 ], glucosidase inhibition [ 15 , 16 ], a threonine tyrosine kinase (TTK) inhibition [ 17 ] and adenosine kinase inhibition [ 18 ]. The pyrimidine moiety has excellent chemical, physical and biological properties, especially when it is combined with heterocyclic compounds, for example: Thieno [2,3-d] pyrimidine is a compound that possesses antioxidant, anticancer, and antitumor properties [ [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that pyrido [2,3- d ] pyrimidine derivatives have important potential in pharmaceutical and medicinal chemistry due to their diverse range of biological activity, including anti-viral properties [ 1 ], antioxidant [ [2] , [3] , [4] , [5] ], antimicrobial [ [6] , [7] , [8] ], anti-inflammatory [ [9] , [10] , [11] ], antitubercular [ 12 ], it is also used as an inhibitor of some enzymes such as dihydrofolate reductase inhibition [ 13 , 14 ], glucosidase inhibition [ 15 , 16 ], a threonine tyrosine kinase (TTK) inhibition [ 17 ] and adenosine kinase inhibition [ 18 ]. The pyrimidine moiety has excellent chemical, physical and biological properties, especially when it is combined with heterocyclic compounds, for example: Thieno [2,3-d] pyrimidine is a compound that possesses antioxidant, anticancer, and antitumor properties [ [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Most heterocyclic compounds possess many biological and pharmacological activities which are including pyrido[2,3‐ d ]pyrimidine derivatives and which inter in the structure of many drugs because they have many biological and pharmacological activities such as antimicrobial [1–3], antioxidant [4–7], antitubercular [8], antiviral [9], anti‐inflammatory [10–12], effective glucosidase inhibitor [13, 14], adenosine kinase inhibitor [15], a dihydrofolate reductase inhibitor [16, 17], and a threonine tyrosine kinase (TTK) inhibitor [18]. In addition, pyrido[2,3‐ d ][1,2,4]triazolo[4,3‐ a ]pyrimidin‐5‐ones are pharmacological scaffold that represent a wide range of biological activities such as analgesic, anti‐inflammatory, anti‐oxidant, and anti‐microbial [19], anti‐HCV, anti‐SSPE, antimicrobial, antioxidant, and antitumor activities [20], peroxynitrite inhibitory activity, anti‐HCV and antioxidant [21], antitumor activity, anti‐HCV [22].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrido [2,3-d]pyrimidine is a privileged heterocyclic scaffold in drug design. Pyrido [2,3-d]pyrimidine ring systems have several biological and pharmacological activities, such as being analgesic, anti-inflammatory [14][15][16][17], anticancer [18], antitubercular [19], antimicrobial [20][21][22], a threonine tyrosine kinase (TT) inhibitor [23], an adenosine kinase inhibitor [24], a dihydrofolate reductase inhibitor [25,26], antiviral [27] and antioxidant [28][29][30].…”
Section: Introductionmentioning
confidence: 99%